Interpretation and Connotation in the Poems "Daddy" and "Tulips" by Slyvia Plath - Nabila, Anisya Zahra; Pertala, Erik Chandra; Hestiana, Siska (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2023)
Poetry is a form of literary work that is very well known and appreciated throughout the world. Famous poetry works are often able to describe the emotions, experiences, and lives of the poets in a very beautiful and poetic way. One of the famous poets whose works are highly adored is Sylvia Plath. Sylvia Plath is known as one of the most talented poets of the 20th century, who managed to capture strong emotional nuances and life experiences in her poems. This research aims to analyze and interpret the meaning of connotation in two of Sylvia Plath's poems, namely "Daddy" and "Tulips". These poems were chosen because they both have different themes and styles, but they both describe the poet's personal feelings and experiences. In this study, qualitative methods were used to collect data from text analysis and interpretation of the connotative meanings contained in the poems. The results of the study show that "Daddy" and "Tulips" have complex meanings and contain many symbols that describe the poet's experiences and emotions. The poem "Daddy" describes Sylvia Plath's feelings of hatred and anger towards her deceased father, while "Tulips" describes the poet's desire to escape feelings of depression and loneliness. Keywords: Interpretation, Connotation, Poetry